The measurement and dimensionality of e-learning blog satisfaction: two-stage development and validation. Issue 5 (19th August 2014) - Wang, Yi-Shun; Li, Ci-Rong; Lin, Hsin-Hui; Shih, Ying-Wei
Abstract : Purpose: The main purpose of the current study is to develop and validate a multi-dimensional instrument to measure e-learning blog satisfaction (ELBS). Design/methodology/approach: This study introduces and defines the construct of e-learning blog satisfaction, provides an empirical validation of the construct and its underlying dimensionality, develops a generic e-learning blog satisfaction instrument with desirable psychometric properties, and investigates the instrument's theoretical and practical applications. Findings: After analyzing data from a calibration sample (n=238) and a validation sample (n=226), this study proposes a 5-factor, 20-item ELBS instrument. Practical implications: This empirically validated instrument will be useful to researchers in terms of developing and testing blog-based learning theories, as well as to educators in terms of understanding students' ELBS and promoting the use of blog-based learning systems. Originality/value: This study is a pioneering effort to develop and validate a multi-dimensional instrument to measure e-learning blog satisfaction.